2009
DOI: 10.1039/b907324h
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopalladated azido complexes containing C,N-donor (HC∼N = 2-(2′-thienyl)pyridine, azobenzene, 3,3′-dimethyl azobenzene, N,N′-dimethylbenzylamine, 2-phenylpyridine) ligands: reactivity towards organic unsaturated compounds and catalytic properties

Abstract: Cyclopalladated azido dimers having various C,N-donor ligands, [Pd(mu-N3)(C,N-Ln)]2 (L1H = 2-(2'-thienyl)pyridine; L2H = azobenzene; L3H = 3,3'-dimethylazobenzene; L4H = N,N'-dimethylbenzylamine; L5H = 2-phenylpyridine), underwent cleavage with tertiary (or chelating) phosphines to form the cyclopalladated [Pd(N3)(PR3)(C,N-L)], the sigma-bonded [Pd(N3)(PR3)2(C-L)], or the dinuclear-cyclopalladated [PdN3(PR3)(C,N-L)]2(mu-P approximately P) complexes. In particular, treating [Pd(mu-N3)(C,N-L)]2 with the basic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…PdA et al have carried out detailed research on Pd-catalyzed CÀ H activation and a reaction mechanism involving a Pd II /Pd IV process was proposed and confirmed. [16] Inspired by Sanfords excellent work, a complex of Pd IV with azobenzene was prepared in situ [16,17] and was then reacted with 2-oxo-2phenylacetic acid (2 a) in DCE at room temperature for 36 h, after which time 3 a was isolated with a yield of 47 % (see the control experiments in Supporting Information for details). Based on the above results, a reaction mechanism involving a Pd II /Pd IV process for this system was proposed and is shown in Scheme 2.…”
Section: Recentlymentioning
confidence: 99%
“…PdA et al have carried out detailed research on Pd-catalyzed CÀ H activation and a reaction mechanism involving a Pd II /Pd IV process was proposed and confirmed. [16] Inspired by Sanfords excellent work, a complex of Pd IV with azobenzene was prepared in situ [16,17] and was then reacted with 2-oxo-2phenylacetic acid (2 a) in DCE at room temperature for 36 h, after which time 3 a was isolated with a yield of 47 % (see the control experiments in Supporting Information for details). Based on the above results, a reaction mechanism involving a Pd II /Pd IV process for this system was proposed and is shown in Scheme 2.…”
Section: Recentlymentioning
confidence: 99%
“…We had reported that Pd­(II)–chloride complexes could undergo facile conversion to the corresponding Pd­(II)–azide complexes by reaction with NaN 3 in an H 2 O/CH 2 Cl 2 two-phase system. , When this method was applied to the chloride-bridged Pd­(II) dinuclear complex [PdCl­(μ-Cl)­(PEt 3 )] 2 ( 3a ), the corresponding azide-bridged Pd­(II) dinuclear complex [Pd­(N 3 )­(μ-N 3 )­(PEt 3 )] 2 ( 4 ) was formed in 47% isolated yield. On the other hand, the reaction of the chloride-bridged Pd­(II) dinuclear complex [PdCl­(μ-Cl)­(PPhMe 2 )] 2 ( 3b ) with NaN 3 in H 2 O/CH 2 Cl 2 did not afford the analogue of 4 but afforded an azide-bridged Pd­(II) tetranuclear complex [Pd­(N 3 )­(μ-N 3 )­(PPhMe 2 )] 4 ( 5 ) in 50% yield.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of phosphide-bridged Pd­(II) complexes was reported first in 1962, and they have been studied extensively since then . However, applications of phosphide-bridged Pd­(II) complexes are sparse, likely because of the challenges in their synthesis due to the handling and sourcing problems associated with hydrophosphines. , The azide-bridged Pd­(II) complexes have also been known since 1968 with a variety of supporting ligands, which include phosphines, π-allyl ligands, imines, and pyridine . However, all of them form a Pd 2 N 2 four-membered ring with azide ligands via the side-on approach, and no other coordination modes are known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneous catalysts are used in the present project. When the reaction was tested at room temperature, the nonpolar solvent toluene gave an excellent yield [42]. The solvents such as THF, 1,4-dioxane, EtOH, H 2 O, and THF/H 2 O=2:1 also afforded low yields of the coupling product.…”
Section: Suzuki−miyaura Carbon-carbon Coupling Reactionmentioning
confidence: 99%